ISTRAŽIVANJE UTICAJA SOCIODEMOGRAFSKIH KARAKTERISTIKA TURISTA NA ODABIR TURISTIČKE DESTINACIJE U USLOVIMA PANDEMIJE COVID-19 - Kostić, Sara; Kovačević Berleković, Bojana (International Journal of Economic Practice and Policy, 2022)
Socio-demographic characteristics are proven vital in terms of different elements associated with choosing a tourist destination. The tourism industry in the time of Covid-19 has experienced numerous challenges. This research aims to examine the listed elements in the context of the socio-demographic characteristics of respondents. The research results will answer the question if respondents who planned to spend summer holidays abroad in 2020, and that destination was replaced with a domestic destination, statistically significantly differ by some socio-demographic characteristics in comparison to those that planned to travel abroad and succeeded. The results show no differences in social-demographic characteristics and show that respondents who replaced tourist destinations abroad with a domestic ones are more eager to do that again in the future. Following obtained results of the research, the authors point to key conclusions and recommendations.